Brain Dynamics of Mild Cognitive Impairment (MCI) from EEG Features - Norsiah, Fauzan; Nur Hurunain, Amran (Elsevier Ltd, 2015)
MCI is a clinical state intermediate between elderly normal cognition and dementia featuring cognitive impairment on neuropsychological testing, The purpose of this research is to identify EEG features of MCI in comparison with the normal aging. Mini mental State Examination were used as screening tool from tweenty particaipants and 14 participants were considered normal and 6 MCI. MCI group revealed the increase of beta2 power over the right anterior region in comparison with the normal healthy aging. Both groups showed a predominance distribution of theta and alpha at the frontal regions, but the presence of theta are highest at the parietal and temporal area indicating signs of cognitive decline among the MCI. A reduction of delta at the prefrontal area (F3, Fz, F4) and the central regions (C3, Cz,C4) for the normal suggests associated cognitive decline at the hippocampal area.